Versatile coordination architectures of products generated by the in situ reaction of a doubly bis(2-pyridyl)pyrazolate bridged dinuclear copper(ii) complex with tetracyanoethylene. Issue 12 (20th February 2019) - Ishikawa, Ryuta; Ueno, Shunya; Hamatake, Yumi; Horii, Yoji; Miyazaki, Yuji; Nakano, Motohiro; Noda, Takeshi; Uematsu, Mikoto; Kawata, Satoshi
Abstract : Reaction of doubly bpypz − bridged Cu(ii ) dinuclear complex and TCNE gave three versatile coordination assemblies with TCNE solvolysis derivatives, depending on reaction solvents. Abstract : The reaction of a doubly bis(2-pyridyl)pyrazolate (bpypz − ) bridged dinuclear copper(ii ) complex, [Cu2 (bpypz)2 ] 2+, with neutral tetracyanoethylene (TCNE) results in the formation of [Cu4 (bpypz)4 (TCVA)2 ]·2TCVA (1 ) in tetrahydrofuran (THF), syn -[Cu2 (bpypz)2 (DCNM)2 ] (2 ) in MeOH, and anti -[Cu2 (bpypz)2 (DCNE)2 ] (3 ) in EtOH, where TCVA − = 1, 2, 2-tricyanoethenolate, DCNM − = 2, 2-dicyano-1-methoxyethenolate, and DCNE − = 2, 2-dicyano-1-ethoxyethenolate. The ligands TCVA −, DCME −, and DCNE − in1–3 were formed in situ during the reaction in different solvents, and the ligands were confirmed through infrared spectroscopy, single-crystal X-ray diffraction, and elemental analyses. The single-crystal X-ray structures of1–3 show that each copper(ii ) centre is five-coordinate in an approximately square pyramidal geometry.1 is a discrete dimer-of-dimers type tetranuclear complex with the copper(ii ) centres bridged by two trans -μ2 - N, O -TCVA − .2 and3 are discrete dinuclear complexes. In2, two apically monodentate N -coordinated DCNM − molecules are oriented in a cis manner to one another, consequently adopting a syn -orthogonal configuration. A weak interaction exists between each copper(ii ) centres and the O atoms of the apically coordinated DCNM − molecules of the neighbouring copper(ii ) dinuclear units, resulting in a pseudo one-dimensional ladder-like coordination polymer arrangement. In3, two apically monodentate N -coordinated DCNE − molecules are oriented in a mutually trans manner across the basal plane of [Cu2 (bpypz)2 ] 2+, thereby adopting an anti -orthogonal configuration. Continuous wave X-band electron paramagnetic resonance spectral measurements on finely ground polycrystalline samples of1–3 confirm a thermally depopulated S = 1 triplet state arising from antiferromagnetically coupled two S = 1/2 spins with orthorhombic g values. Variable-temperature dc magnetic susceptibility measurements of1–3 indicate significant antiferromagnetic coupling (quantified by the isotropic spin Hamiltonian, H = −2 JS 1 · S 2, for the two copper(ii ) centres: J = −217.7, −210.3, and −188.5 cm −1 for1, 2 and3, respectively) for the doubly bpypz − bridged copper(ii ) centres.